2017
DOI: 10.1155/2017/6928489
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic Potentiation of Restoration of Visual Function after Optic Nerve Damage in Rats

Abstract: Enhancing cortical plasticity and brain connectivity may improve residual vision following a visual impairment. Since acetylcholine plays an important role in attention and neuronal plasticity, we explored whether potentiation of the cholinergic transmission has an effect on the visual function restoration. To this end, we evaluated for 4 weeks the effect of the acetylcholinesterase inhibitor donepezil on brightness discrimination, visually evoked potentials, and visual cortex reactivity after a bilateral and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 79 publications
(86 reference statements)
0
10
0
Order By: Relevance
“…Specifically, repeated days of cholinergic enhancement has been shown to improve visual perceptual learning for a number of tasks in observers with normal vision (Rokem and Silver, 2010; Kang et al, 2014; Chamoun et al, 2017a), suggesting a central role of the neurotransmitter in modulating plasticity processes. In the rat, cholinergic potentiation also improves visual recovery (Chamoun et al, 2017b) and visual processing (Soma et al, 2013; Kang et al, 2015; Chamoun et al, 2016), due, in part, to enhancing the responsiveness of visual neurons to their tuned stimuli. Based on these findings, we expected a reinforcement of the shift in perceptual eye dominance in favor of the deprived eye.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, repeated days of cholinergic enhancement has been shown to improve visual perceptual learning for a number of tasks in observers with normal vision (Rokem and Silver, 2010; Kang et al, 2014; Chamoun et al, 2017a), suggesting a central role of the neurotransmitter in modulating plasticity processes. In the rat, cholinergic potentiation also improves visual recovery (Chamoun et al, 2017b) and visual processing (Soma et al, 2013; Kang et al, 2015; Chamoun et al, 2016), due, in part, to enhancing the responsiveness of visual neurons to their tuned stimuli. Based on these findings, we expected a reinforcement of the shift in perceptual eye dominance in favor of the deprived eye.…”
Section: Discussionmentioning
confidence: 99%
“…Following surgery, mice did not exhibit any abnormal eating and drinking behavior. The optic nerves of both eyes were crushed in agreement with previous studies [25,26] and the effects of ONC in operated and in control mice were then compared. In this respect, there are some limitations to the use of the non-damaged eye as an internal control for a number of reasons.…”
Section: Optic Nerve Crush (Onc)mentioning
confidence: 99%
“…Similarly, our mice did not appear to detect the cliff as indicated by the loss of avoidance behaviors during the visual cliff test. Previous rat studies showed a disconnection between behavior and anatomical or electrophysiological changes following damage to the optic nerve 9 . In these studies, it was shown that even with only 10% of functional retinal ganglion cells, the animals were able to perform close to normal in behavioral visual tasks 26 .…”
Section: The Onc Induces Visual Behavioral Alterationsmentioning
confidence: 91%
“…This recovery is in agreement with previous autoradiographic studies after an ONC in rats 26 . Other studies were unable to observe an improvement in cortical activity following an ONC using visual evoked potential (VEP) recordings 9,27,28 in anesthetized rats. The calcium signal of GCAMP6s mice mainly arises from the Thy-1 long-projecting excitatory neurons and is not detected in GABAergic cells 29 .…”
Section: The Onc Induces a Visual Impairment Followed By A Gradual Rementioning
confidence: 98%
See 1 more Smart Citation